2022
DOI: 10.56899/151.6a.13
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Structural, Physicochemical, Pharmacokinetics, PASS Prediction, and Molecular Docking Analysis of Methyl 6-O-Myristoyl-α-D -Glucopyranoside Derivatives against SARS-CoV-2

Abstract: Monosaccharide derivatives are of importance in the field of carbohydrate chemistry because of their effectiveness in the synthesis of biologically active products. As a consequence, the chemistry and biochemistry of carbohydrate derivatives are an essential part of biochemical and medicinal research. In this work, we have explored the speciation of acylated methyl 6-O-myristoyl-α-D-glucopyranoside derivatives (2−9) to find the pharmacodynamics, toxicity profiles, and biological activities by using ADMET studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Frequency calculations were also carried out to confirm that all structures were in their energy minima. Previous studies [46] , [47] , [48] , [49] , [50] , [51] , [52] have demonstrated the accuracy and efficiency of using the B3LYP/6–31G(d,p) level of theory. The analysis of frontier molecular orbital (FMO) energy distribution, spanning from the highest occupied molecular orbital (HOMO) to the lowest unoccupied molecular orbital (LUMO), along with the generation of molecular electrostatic potential (MEP) maps, was performed using GaussView 6 software.…”
Section: Methodsmentioning
confidence: 99%
“…Frequency calculations were also carried out to confirm that all structures were in their energy minima. Previous studies [46] , [47] , [48] , [49] , [50] , [51] , [52] have demonstrated the accuracy and efficiency of using the B3LYP/6–31G(d,p) level of theory. The analysis of frontier molecular orbital (FMO) energy distribution, spanning from the highest occupied molecular orbital (HOMO) to the lowest unoccupied molecular orbital (LUMO), along with the generation of molecular electrostatic potential (MEP) maps, was performed using GaussView 6 software.…”
Section: Methodsmentioning
confidence: 99%
“…39 The geometries and vibrational wave numbers of benzylidenemalononitrile and ethyl 2-cyano-3-phenylacrylate derivatives ( 1 – 6 ) were optimized using the B3LYP/6-31G(d,p) level of theory. The prior research 40 that our group conducted consisted of exploring the deamination reactions of a variety of different nitrogenous bases using a variety of different computational methodologies. The results obtained from G3MP2, G3MP2B3, G4MP2, G3B3, and CBS-QB3 methods agreed with each other within a range of 10 kJ mol –1 , while the B3LYP/6-31G(d,p) method had a deviation of up to 18 kJ mol –1 .…”
Section: Materials and Methodsmentioning
confidence: 99%
“…The chemical reactivity indicators, such as HOMO, LUMO and gap energies were also evaluated [ 41 , 42 ]. Molecular docking studies performed on pathogenic fungal and bacterial proteins have helped to obtain more information about the biological applications of synthesized molecules [ 43 , 44 ]. Thus, their binding affinity and abilities with fungal proteins (PDB: 1KS5, 1R51) and bacterial proteins (PDB: 4A1J, 5IQR) were assessed, whereby the binding mode was then identified.…”
Section: Introductionmentioning
confidence: 99%